Implementasi Permendikbud Nomor 24 Tahun 2007 Tentang Standar Sarana dan Prasarana Pendidikan - Rakista, Putri Mutiara (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
Standards for educational facilities and infrastructure are the minimum facilities that need to be owned by each educational unit in carrying out educational activities. Permendikud Number 24 of 2007 as a form of government effort to make education facilities equal. However, even though the government has launched policies related to standards for educational facilities and infrastructure, it is still not evenly distributed, so this has an impact on low student learning outcomes due to a lack of completeness of education in schools. The research method uses descriptive qualitative while the data collection techniques used are observation, interviews and documentation. The analysis technique used in this research is qualitative data analysis technique. The results showed that the policy on educational facilities and infrastructure standards for elementary education at the junior high school level in Tasikmalaya City in several schools had not been fulfilled in accordance with Permendikbud Number 24 of 2007, such as the library room, science laboratory room, computer laboratory room, laboratory equipment, sports equipment and art equipment